The effect of Rhodiola rosea supplementation on endurance performance and related biomarkers: a systematic review and meta-analysis - Wang, Xiaolin; Yang, Xuezhen; Gao, Zhendong; Zeng, Jin; Liu, Yutong (Frontiers in Nutrition, 2025)
This meta-analysis aimed to evaluate the effects of Rhodiola rosea L. (RR) supplementation on endurance performance and key physiological biomarkers, including oxidative stress, muscle damage, inflammation, and metabolic markers. A systematic search of Web of Science, PubMed, Scopus, EBSCO, and CNKI identified randomized controlled trials published up to March 20, 2025. Random-effects meta-analyses were conducted using R software, and methodological quality was appraised using the Physiotherapy Evidence Database scale. Additionally, subgroup analyses assessed the moderating effects of daily RR dosage, training duration, and training status. A total of 26 randomized controlled trials were included, involving 668 healthy participants with a mean age of 22.0 ± 10.7 years. The mean intervention duration was 33 days, with outcome assessments conducted from immediate post-exercise through 24-hour follow-up. The results indicated that RR supplementation significantly improved endurance-related outcomes, including VO2max (11 studies; ES = 0.32, p < 0.01), time to exhaustion (TTE; 7 studies; ES = 0.38, p < 0.05), and time trial performance (TTP; 5 studies; ES = −0.40, p < 0.05). Antioxidant capacity was enhanced, with increases in total antioxidant capacity (TAC; 6 studies; ES = 0.59, p < 0.05) and superoxide dismutase (SOD; 7 studies; ES = 1.16, p < 0.01), alongside reductions in malondialdehyde (MDA; 6 studies; ES = −1.21, p < 0.001). RR also reduced creatine kinase (CK; 9 studies; ES = −0.84, p < 0.01) and lactate levels (LA; 7 studies; ES = −0.87, p < 0.05), indicating improved metabolic efficiency. No significant effects were observed on inflammatory markers, including interleukin-6 (IL-6) and C-reactive protein (CRP). Subgroup analyses indicated greater VO2max improvements at doses >600 mg/day, with trained individuals exhibiting lower CK levels and more pronounced reductions in CK at early follow-up assessments (≤15 min) post-exercise. In conclusion, RR supplementation is an effective ergogenic aid for enhancing endurance performance and improving physiological biomarkers related to oxidative stress, muscle damage, and metabolic efficiency, though heterogeneity across studies warrants cautious interpretation.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO CRD42024619014.